New Stream of The Indonesian Economy: Economic Empowerment and Islamic Entrepreneurship Culture In Islamic Boarding School : Arus Baru Ekonomi Indonesia: Pemberdayaan Ekonomi dan Budaya Kewirausahaan di Pondok Pesantren - Nurohman, Dede; Haque , Ahasanul; Suselo , Dedi; Akhyak (International Journal of Islamic Business and Economics (IJIBEC), 2023)
This paper aims to reveal the empowerment process carried out by BLKK Islamic boarding school and diagnose potential aspects that can be developed in realizing the goal of economic empowerment of Islamic boarding schools. This type of research is field research using a qualitative approach with locus on seven BLKK Islamic boarding schools in four regions, namely; district and city of Blitar, city of Kediri, district of Tulungagung, and district of Trenggalek. Through Kurt Lewin's theory of social change which includes three stages; unfreezing, moving, and refreezing, this paper finds that in the unfreezing and moving stages, all BLKK Islamic Boarding Schools are running well as program assistance is still running. However, at the refreezing stage, many BLKKs were difficult to develop. Because this stage needs to a spirit of entrepreneurship and independence that can take advantage of the existing potential, such as; the open mind set of the Islamic boarding school, the figures and influence of the kiai who can expand the external collaboration network, spreading alumni throughout the communities, and the BLKK building and equipment used as a production house and a place to improve the quality of human resources. The implication is the importance of the entrepreneurial attitude of Islamic boarding school BLKK managers in realizing the economic empowerment of Islamic boarding schools